An Analysis of the Relationship Between Job Satisfaction and Organizational Commitment and Its Effect on Employee Turnover Intention at Universitas Amikom Yogyakarta - Eny Ariyanto; Suyatmi, Suyatmi; Nurhayanto, Nurhayanto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze the relationship between job satisfaction and organizational commitment, as well as their influence on turnover intention among employees at Universitas Amikom Yogyakarta. The study uses a quantitative approach with the survey method, involving 38 respondents selected through simple random sampling. Hypothesis testing uses correlation and linear regression analysis techniques, which are processed with SPSS 22. The results show that job satisfaction has a positive yet weak influence on organizational commitment, with a coefficient determination (R2) of 29.8%. This indicates that job satisfaction explains only a small portion of the variance in organizational commitment. Furthermore, job satisfaction has been found to have a negative but insignificant effect on turnover intention, indicating that the level of employee job satisfaction is not a strong factor in reducing employees’ intention to leave the organization. Similarly, organizational commitment also exhibited a negative but insignificant effect on turnover intention. Simultaneously, the influence of job satisfaction and organizational commitment on turnover intention produced a coefficient of determination (R²) of 0.127, indicating that both variables explain only 12.7% of the variation in turnover intention. These findings indicate the need to consider other, more dominant factors related to employee turnover intention at Universitas Amikom Yogyakarta.